Sistema integrado para mejorar la gestión de información de la unidad del serenazgo de la Municipalidad Provincial de Maynas 2022 - Rodriguez Zumaeta, Karla Danixa (2022)
The purpose of this research work is to develop an integrated system that allows improving the information management of incidents in the serenazgo unit of the Provincial Municipality of Maynas in the year 2022, this research is of an application type with a descriptive level and with a design. non-experimental, the study sample will be made up of 49 watchmen who work in the serenazgo unit of the provincial municipality of Maynas and for this, probabilistic sampling was used. The method of collecting information that was used was the survey using the survey technique through a questionnaire where the time it takes to perform the process of registering incidents, the time of searching for incidents and the time in the generation of the reports of the incidents, in this context it was possible to contrast and accept the specific hypotheses of the investigation: The use of the integrated system will allow to improve the time of registration of incidents of the serenazgo unit of the provincial municipality of Maynas – 2022, The use of the integrated system will allow to improve the time of the search for information on incidents of the serenazgo unit of the provincial municipality of Maynas – 2022, The use of the integrated system will allow to improve the time in the generation of reports of the incidents of the serenazgo unit of the provincial municipality of Maynas - 2022.